Regionalism in Africa: Concepts and context - (:unkn) unknown (My University, 2013)
Until the early 1990s such notions as rule of law, good governance and security were conspicuously absent from the mandates of Africa’s regional and sub-regional organizations that were originally to focus exclusively on economic integration. This chapter traces the overall evolution of regionalism in Africa, from its initial emphasis on regional economic integration to its current focus on regional security. The following chapters in the book, after taking a closer look at the African Union, will then discuss the Economic Community of West African States (ECOWAS), the Southern African Development Community (SADC), the Inter-Governmental Authority on Development (IGAD) and the Economic Community of Central African States (ECCAS).
Keywords: African Research